The Hegemony of The Exxonmobil and Freeport Contract in Investing in Indonesia and Also The Abandonment of The Local People’s Health Rights (Indian Journal of Forensic Medicine & Toxicology, 2020)
The type of contract carried out nowadays, which is the Product Sharing Contract (PSC) and contract of work in the natural resource sector results to product sharing, which is on one hand thought to not yet fulfill the principle of justice for the state. On the other hand, the government still needs funds from foreign investors to carry out economic development. The balancing position between the foreign investment and the domestic investment in the capital market investment in the oil, gas, and the gold-copper mining sector of Freeport in Papua and Exxonmobil in Indonesia shows a foreign domination. It means that there is a natural resource sector investment hegemony by foreign investors. The implication of this condition is the lightening burden of the state budget, the increase of workforce absorbment and the transfer of technology. It also causes opportunity cost. There is the environmental destruction, including the aspect of healthcare for the local people in the mining location as a compensation. For that, the government needs to review the contract regulation for these two natural resources and revise what is necessary.
Keywords: hegemony, investment, contract of work, production, product sharing contract, health.